2018
DOI: 10.1021/acscatal.8b04098
|View full text |Cite
|
Sign up to set email alerts
|

Phenol-Directed C–H Functionalization

Abstract: Phenols are important starting materials, intermediates, and functional elements of a very broad range of chemicals and materials. They are large-volume products of benzene oxidation and are increasingly available from biomass. Investment in methodologies that improve the efficiency of their use can have both immediate and future impacts on chemical upgrading. This review summarizes recent phenol-directed C–H functionalization reactions, which provide efficient increases in molecular complexity. Catalytic meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
142
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(147 citation statements)
references
References 273 publications
0
142
0
5
Order By: Relevance
“…Moreover, as mentioned above, it has been reported that the presence of certain reductive intermediates, such as hydroquinone or catechol, play an important role in the Fenton mechanism [77]. Therefore, these intermediates could accelerate the H 2 O 2 decomposition during the oxidation of OII.…”
Section: 222mentioning
confidence: 93%
“…Moreover, as mentioned above, it has been reported that the presence of certain reductive intermediates, such as hydroquinone or catechol, play an important role in the Fenton mechanism [77]. Therefore, these intermediates could accelerate the H 2 O 2 decomposition during the oxidation of OII.…”
Section: 222mentioning
confidence: 93%
“…[147] Dirigierte Alkylierungen von Phenolen gehen oft mit mçglichen viergliedrigen Metallacyclen einher, weshalb die Rolle der Hydroxygruppe als dirigierende Gruppe fraglich ist. Dirigierte C-H-Alkylierungen bieten eine effiziente Alternative,d ie -z umindest teilweise -e inige dieser Einschränkungen umgeht; sie werden in diesem Abschnitt zusammengefasst.…”
Section: Phenole Und Derivate Als Dirigierende Gruppenunclassified
“…Beispiele sind:Dicumyl-oder Di-tert-butylperoxid (mithilfe von Palladiumkatalyse), [186] Carbonsäuren (mithilfe von Palladiumkatalyse) und Cycloalkane (mithilfe von Rutheniumkatalyse), [147] die allerdings in den meisten Fällen Gemische aus mono-und dialkylierten Produkten ergeben;T oluolderivate, die abhängig von dem fürd as Ruthenium verwendeten Liganden zur regioselektiven Einführung von Benzylgruppen in ortho- [187a] oder meta-Position [187a,b] eingesetzt werden kçnnen; sowie a-Carbonylsulfoxonium-Ylide,d ie effizient ein Methylenketon ortho zu verschiedenen dirigierenden Gruppen (Pyridin, Pyrimidin, Chinolin und Pyrazol) in Gegenwart eines Rhodium- [188a,b] oder Cobaltkatalysators [188c] einführen. Beispiele sind:Dicumyl-oder Di-tert-butylperoxid (mithilfe von Palladiumkatalyse), [186] Carbonsäuren (mithilfe von Palladiumkatalyse) und Cycloalkane (mithilfe von Rutheniumkatalyse), [147] die allerdings in den meisten Fällen Gemische aus mono-und dialkylierten Produkten ergeben;T oluolderivate, die abhängig von dem fürd as Ruthenium verwendeten Liganden zur regioselektiven Einführung von Benzylgruppen in ortho- [187a] oder meta-Position [187a,b] eingesetzt werden kçnnen; sowie a-Carbonylsulfoxonium-Ylide,d ie effizient ein Methylenketon ortho zu verschiedenen dirigierenden Gruppen (Pyridin, Pyrimidin, Chinolin und Pyrazol) in Gegenwart eines Rhodium- [188a,b] oder Cobaltkatalysators [188c] einführen.…”
Section: Alkylierung Mit Anderen Reagentienunclassified
“…[1][2][3][4][5][6][7][8][9][10][11] To obtain good dispersibility of NPs, the surface of metal NPs are directly modified with organic materials or the NPs are mixed with dispersion media such as fatty acids and amines with long alkyl chains. Owing to the unique surface structure derived from their fine primary particles, the TiO 2 nanoparticle assemblies show excellent dispersion ability of Au nanoparticles on their rough surface.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] To obtain good dispersibility of NPs, the surface of metal NPs are directly modified with organic materials or the NPs are mixed with dispersion media such as fatty acids and amines with long alkyl chains. [1][2][3][4][5][6][7][8][9][10][11] To obtain good dispersibility of NPs, the surface of metal NPs are directly modified with organic materials or the NPs are mixed with dispersion media such as fatty acids and amines with long alkyl chains.…”
mentioning
confidence: 99%